Verdade, ficção e memórias da violência na narrativa de Valêncio Xavier - Fernanda Valim Côrtes Miguel (Estudos de Literatura Brasileira Contemporânea)
This article aims to reflect on the whole work Rremembranças da menina de rua morta nua e outros livros (2006) from some of the seven stories that make up this publica- tion. Taking the narrative as a starting point, we will point traces of memories of systemic and salable social violence, marked by poverty, exploitation and human misery. We also part from the attempt to recover and discuss some aspects of the complex theoretical discussion that takes place between literature, history and writing. This reflection parts from the purpose of construction of knowledge in support of the work with the historical dimension of literary texts, trying to point to a possible dissolution of the binary and rigid boundaries which sometimes are established between these fields.